Optimizing Turbidity Reduction in Tofu Industry Wastewater Using Alum Coagulant - Findia Wulan Djari; Rezania Asyfiradayati (International Journal of Health and Pharmaceutical (IJHP), 2024)
The liquid waste generated by the tofu industry is a significant environmental pollutant, particularly contributing to turbidity in rivers, lakes, and other water bodies. One effective method to address this issue is the treatment of wastewater using alum coagulant. This study aimed to assess the turbidity levels of tofu industry wastewater before and after the application of alum coagulant, as well as to determine the optimal dose or concentration of the coagulant. Conducted in January 2024 at the Public Health Laboratory of Universitas Muhammadiyah Surakarta, this research employed a quantitative approach with a quasi-experimental design. The data analysis utilized quantitative methods, specifically the ANOVA test, to evaluate the effectiveness of the alum coagulant. The findings revealed that turbidity levels in the tofu industry wastewater decreased following the coagulation process: a concentration of 2 ml resulted in a 22.93% reduction, 4 ml led to a 26.24% decrease, 6 ml achieved a 29.08% reduction, and 8 ml produced a 36.41% decrease. Therefore, the optimal concentration of alum coagulant for effectively reducing turbidity in tofu industry wastewater is determined to be 8 ml, as it demonstrated the highest effectiveness in lowering turbidity levels.